Trial of Deferiprone in Parkinson’s Disease - Devos, David; Labreuche, Julien; Rascol, Olivier; Corvol, Jean-Christophe; Duhamel, Alain; Guyon Delannoy, Pauline; Poewe, Werner; Compta, Yaroslau; Pavese, Nicola; Růžička, Evžen; Dušek, Petr; Post, Bart; et al. (The New England journal of medicine, 2022)
Iron deposition in the substantia nigra has been implicated in Parkinson’s disease. Chelation with deferiprone reduced brain iron content but led to worse scores on scales of the movement disorder at 36 weeks.